Research on Timing Chain Wear Performance of the Engine - Yin Ziming; Li Jiawang; Cao Chao; Wu Dao (Jixie chuandong)
Through the analysis of the chain failure mode， the main factors that causing the chain elongation is found. Through the validation on the acceleration-fatigue test rig， the chain using vanadinizing pins is more better than carbon-nitrogen and chromizing pins on the chain wear-resistant characteristics. After using vanadinizing pin chain， the problems of the engine project which has the chain severely worn issues is solved. The conclusions and test method has a certain kind of reference on the chain system development and application on the engine.